Characterization of 4-coumarate: Coenzyme a ligase from Boesenbergia rotunda / Nabeel Ata Abdul Muneim - Nabeel Ata , Abdul Muneim (2017)
Boesenbergia rotunda, formerly known as Kaempferia pandurata Roxb. or Boesenbergia pandurata (Roxb. Schltr), is a small perennial monocotyledonous plant belonging to the Zingiberaceae family. One of the important secondary metabolites produces by B. rotunda is flavonoids which derived from phenylpropanoid metabolisms. These compounds are essential for plant growth and development and have been used for biomedical applications. One of the key enzymes in the phenylpropanoid metabolism, 4-coumarate: coenzyme A ligase (4CL), is yet to be characterized. In this study, B. rotunda cell suspension cultures were first treated with phenylalanine precursor and the expression level of 4CL was analyzed to determine the role of 4CL in the production of flavonoids. In Real-time analysis, results show that the 4CL transcript level for 14- and 10-day old phenylalanine-treated cultures were up-regulated to 22- and 17-fold, respectively, compared to 0-day, indicating the promotive effect of phenylalanine in enhancing the 4CL expression. cDNA for 4CL was then isolated and characterized from B. rotunda cell suspension cultures using combined methods of RACE and Degenerate Primers. The isolated 4CL cDNA sequence consists of 1,578 bp open reading frame (ORF) which encoding 526 amino acids with a similarity of 82% to 4-coumarate-CoA ligase 1-like [Musa acuminata subsp. malaccensis]. Sequence analysis showed that the 4CL contains AMP-binding domain (PFSSGTTGLPKGV), GEICIRG motif and conserved VPP and PVL domains. The 4CL coding sequence was then transformed into Escherichia coli strain BL2 (DE3) and analyzed its protein expression by SDS‐PAGE. Our preliminary protein expression result shows that the 4CL was successfully expressed in E.coli. These findings merit further studies such as overexpression of 4CL gene in B. rotunda to enhance the flavonoid production.